MULTILINGUALISM IN GERMANY: POTENTIAL AND CHALLENGES FOR SOCIETY AND INDIVIDUALS - Susanne R. Borgwaldt (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
After a general introduction, multilingualism in Germany will be discussed with respect to three main aspects: (a) demographics and development of multilingualism (b) the public view regarding multilingualism and (c) types of multilingualism. Keywords: challenge, demography, multilingual,